2015
DOI: 10.1037/cdp0000047
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity as a moderator of how parents’ attitudes and perceived stigma influence intentions to seek child mental health services.

Abstract: Ethnicity deferentially impacts attitudes and stigma associated with seeking mental health services. Public education efforts to increase service use should be tailored toward under-served groups to be more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 46 publications
1
46
0
1
Order By: Relevance
“…Conversely, among parents who did not report any stigma, half of parents also had received mental health services, however in this case all of the Latinos in this group had received mental health services. These findings are consistent with recent survey studies of caregivers, where stigma was associated with a lower parent-reported likelihood of help seeking for Latino parents, but not for non-Latino White or African American parents (Turner et al, 2015). Further review of the themes across ethnic groups revealed that Latinos more often endorsed Parent Internalized Stigma , such as believing that their child would be perceived as “crazy,” and seeing this as a deterrent to seeking mental health treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Conversely, among parents who did not report any stigma, half of parents also had received mental health services, however in this case all of the Latinos in this group had received mental health services. These findings are consistent with recent survey studies of caregivers, where stigma was associated with a lower parent-reported likelihood of help seeking for Latino parents, but not for non-Latino White or African American parents (Turner et al, 2015). Further review of the themes across ethnic groups revealed that Latinos more often endorsed Parent Internalized Stigma , such as believing that their child would be perceived as “crazy,” and seeing this as a deterrent to seeking mental health treatment.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in a study of 238 caregivers, stigma was associated with a lower parent-reported likelihood of help-seeking for Hispanic Americans, but not for European Americans or African Americans (Turner, Jensen-Doss, & Heffer, 2015). In another quantitative study, caregivers ( n = 275) reported more socioeconomic and stigma-related barriers to obtaining mental health services than medical services, and Hispanic parents reported these barriers as more inhibiting than did African-American parents (Young & Rabiner, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential that practitioners who work with these populations consider how caregivers who are affected by larger structural inequalities, such as racism and other forms of discrimination, make meaning of and navigate these experiences (Chu, Leino, Pflum, & Sue, ). Similarly, practitioners should be trained to have fundamental understandings of essential elements of cultures, such as respeto in Latinx culture, and consider how to adapt services to be responsive to families’ unique challenges, priorities, and needs, including concerns about stigma (Turner, Jensen‐Doss, & Heffer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that psychiatric conditions were more commonly reported by families and documented by clinicians for white patients is consistent with a large body of evidence showing that racial or ethnic minority patients experience more stigma related to mental health diagnoses and use mental health services less. [29][30][31][32][33] Families were more likely to report use of mental health services than a known mental health diagnosis. This finding may reflect families' willingness to use services even if they do not understand or experience stigma related to psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 99%